Administration of oxytocin antagonist at the same time as using a Foley catheter with cotton swab before embryo transfer for cervical stenosis - Heesuk Chae (BMC, 2021)
Abstract Background Embryo transfer without difficulty in a patient with cervical stenosis can be a great challenge for in vitro fertilization (IVF). We report a successful pregnancy following a frozen thawed embryo transfer after administration of an oxytocin antagonist at the same time as using a Foley catheter with cotton swab in a patient with refractory cervical stenosis. Case presentation A 40-year-old woman undergoing IVF. The patient's previous embryo transfers were difficult. For every transfer, uterine manipulation was needed, force was required, and dilatation was necessary. A Foley catheter with a cotton swab was inserted into the cervical canal, atosiban was administered at the same time, and the Foley catheter was removed immediately before embryo transfer. A smooth transfer was performed without bleeding, force, uterine manipulation, or cervical dilator. The patient became pregnant and delivered by cesarean section at term. Conclusion This method is effective in performing atraumatic embryo transfer in patients with cervical stenosis.